2011
DOI: 10.1063/1.3595485
|View full text |Cite
|
Sign up to set email alerts
|

Self-heating in piezoresistive cantilevers

Abstract: We report experiments and models of self-heating in piezoresistive microcantilevers that show how cantilever measurement resolution depends on the thermal properties of the surrounding fluid. The predicted cantilever temperature rise from a finite difference model is compared with detailed temperature measurements on fabricated devices. Increasing the fluid thermal conductivity allows for lower temperature operation for a given power dissipation, leading to lower force and displacement noise. The force noise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…(b) The corresponding temperature increase is calculated from the calibrated piezoresistor TCR. The average piezoresistor temperature predicted by a finite difference-based thermal model [12] (dashed lines) matches the experimental data to within about 20%. (c) The validated model is used to predict the maximum and tip temperatures during operation at a 1 V bridge bias.…”
Section: Figurementioning
confidence: 77%
See 2 more Smart Citations
“…(b) The corresponding temperature increase is calculated from the calibrated piezoresistor TCR. The average piezoresistor temperature predicted by a finite difference-based thermal model [12] (dashed lines) matches the experimental data to within about 20%. (c) The validated model is used to predict the maximum and tip temperatures during operation at a 1 V bridge bias.…”
Section: Figurementioning
confidence: 77%
“…We opted for a cantilever beam thickness of 300 nm because the reduction in thermal conductivity [9] and uncertainty in the effective elastic modulus [10, 11] of thinner probes lead to diminishing performance returns for piezoresistive cantilevers [12]. …”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…For a complete review of the main papers published on this topic, the reader is referred to (Khanafer and Vafai 2010) where it can be observed that the coupling of thermal-fluid-solid interactions is a challenging task that has not yet been accurately solved. A common practice is the imposing of a constant temperature at the fluid-solid interface Doll et al 2011), or a constant heat transfer coefficient to investigate the temperature distribution in the solid domain (Mohd and Ansari 2012). This paper proposes a simple methodology to solve the thermal FSI problems in heated micro-cantilevers based on the standard two-way coupling approach: the fluid package solves the Navier-Stokes equations and obtains the fluid force and the heat flux over the solid boundary.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…Treatise encompasses a few examples where researchers have investigated the thermal drift in piezoresistive cantilever sensors through theoretical modeling [17][18][19] and experimental studies. [20][21][22][23][24][25] Theoretical studies have primarily focused on the impact of the piezoresistor dimensions and the external voltage supply on the thermal drift. Moreover, reported mathematical models have not only neglected the influence of cantilever dimensions and the constituent layers but also overlooked the interdependence of electrical, mechanical and thermal design parameters in determining the performance of the sensors.…”
Section: Introductionmentioning
confidence: 99%